Land use system, invasive species and shrub diversity of the riparian ecological infrastructure determine the specific and functional richness of ant communities in Mediterranean river valleys. (December 2022) - Zina, Vera; Duarte, Gonçalo; Fonseca, André; Conde, Sofia; Teresa Ferreira, Maria; Carlos Franco, José; Rosário Fernandes, Maria
Highlights: Land use was the main driver of ant richness in riparian ecological infrastructures. Shrub richness promoted animal and plant community regulation services. Proximity to urban areas affected scavenger ant species in woody patches. Forest production system had the highest capacity to provide ant-mediated functions. Argentine ant impacted native ant species in Agroforestry and Irrigated cropland. Graphical abstract: Abstract: The Riparian Ecological Infrastructure (REI) is defined by the ensemble of natural and semi-natural woody and herbaceous vegetation patches located contiguously to water courses. Freshwater environments and the associated REI provide habitat for many species, acting as corridors linking landscapes at a wider scale. Focusing on ants, a ubiquitous and diverse group of insects that provide a large number of ecosystem roles, we address the relative importance of REI-related local and landscape factors that drive the species and functional richness of ant communities. The study was conducted in 2019, at 100 sites in central Portugal, in Tagus and Sorraia irrigated valleys, comprising three landscape systems, namely, Forest production, Agroforestry and Irrigated cropland. Four major types of variables were used to characterize the sampling patches, including the landscape system, patch typology, spatial configuration and habitat quality. Ants were collected using pitfall traps and species composition was used to classify functional groups. Using an extensive survey, machine learning methods were used to identify the relative importance of REI-related variables in explaining ant specific and functional richness. Results indicated that ant biodiversity was primarily explained by the 'Landscape system' and the 'Argentine ant abundance'. Nevertheless, 'Shrub richness' was selected as an important variable to enhance 'Animal community regulation' and 'Plant community regulation' functional groups, while herbaceous patches appeared to be relevant for the 'Decomposition through scavenging' group. The highest ant biodiversity was found in the Forest production 'Landscape system', where patches were larger, more complex and less fragmented, showing high habitat quality associated with a reduced abundance of the invasive Argentine ant. Contrarily, the lowest was expected in the Intensive cropland 'Landscape system', where the REI is highly fragmented, showing low habitat quality and suffering from a high Argentine ant invasion, as a result of high human pressure. The Agroforestry 'Landscape system' showed moderate ant biodiversity, mainly associated with patches characterized by low strata complexity and shrub cover densities, due to understory clearing and grazing activities.